2021
DOI: 10.1097/scs.0000000000007593
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Surgery-Related Hashtag Utilisation on Instagram

Abstract: Background: Patients, parents, and carers are increasingly using social media to access and contribute to health information. There are currently 3.484 billion active social media users. Instagram is a primarily visual social media platform for sharing photographs and videos with currently over one billion monthly active users. Limited research has investigated the use of Instagram in healthcare contexts including plastic surgery, and in the treatment of specific conditions, such as fibromyalgia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…The current literature highlights the increased use of social media to share and connect individuals who are interested or who require procedures in specialties such as general surgery, craniofacial surgery, gynecological surgery, orthopedic surgery, and neurosurgery. 11–15 As of recent date, the spread of plastic surgery procedures through Instagram profiles, hashtags, and search terms has gained popularity as a valid channel for promotion. In this study, we hypothesize that as a result of increased medical marketing on Instagram, there is an increase in public interest in plastic surgery elective procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature highlights the increased use of social media to share and connect individuals who are interested or who require procedures in specialties such as general surgery, craniofacial surgery, gynecological surgery, orthopedic surgery, and neurosurgery. 11–15 As of recent date, the spread of plastic surgery procedures through Instagram profiles, hashtags, and search terms has gained popularity as a valid channel for promotion. In this study, we hypothesize that as a result of increased medical marketing on Instagram, there is an increase in public interest in plastic surgery elective procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Such activities include creating false accounts and purchasing “likes” or “tweets”. Finally, AAS fails to capture activity from social media platforms such as Instagram (Menlo Park, CA) and TikTok (Culver City, CA), which have become increasingly integral to the dissemination of information pertaining to plastic surgery 31–33. Since these data are proprietary, their collection was particularly difficult, provided the scope of this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, AAS fails to capture activity from social media platforms such as Instagram (Menlo Park, CA) and TikTok (Culver City, CA), which have become increasingly integral to the dissemination of information pertaining to plastic surgery. [31][32][33] Since these data are proprietary, their collection was particularly difficult, provided the scope of this investigation. AAS, therefore, should be utilized in conjunction with traditional bibliometrics to achieve a more complete understanding of research impact.…”
Section: Discussionmentioning
confidence: 99%
“…Within this dataset, we screened the top ten posts associated with each queried hashtag at one time and one geographical location. Although a similar strategy has been used in previous literature, 13,18,30 We recognize that there may be a potential bias in the hashtags we selected.…”
Section: Previous Studies Examined Posting About Clear Aligners Onmentioning
confidence: 99%
“…Previous studies have revealed that more than one-third of educational content shared on social media concerning cleft lip and/or palate exhibited poor quality, and approximately 80% of tweets authored by laypersons employing keywords such as 'plastic surgery' or #plasticsurgery were found to be factually inaccurate. 17,18 The content of orthodontic-related posts has been investigated on different social media platforms. [19][20][21][22][23] We previously explored the benefits of using Twitter in disseminating orthodontic clinical and research information.…”
Section: Introductionmentioning
confidence: 99%